Strategi Learning and Development dalam Penguatan Kinerja Operator Call Center 110: Studi Kasus Polres Bogor - Ananta Brima Yoga; Adi Ageng Rismoko; Gita Sulika Sari (JOM, 2026)
The 110 Call Center Service stands at the frontline of the digital transformation of the Indonesian National Police (Polri) in actualizing responsive public services. High operational workloads subject operators to extreme cognitive pressure and psychological vulnerability. This study aims to analyze the workload dynamics and formulate a human resource development strategy through a Learning and Development (L&D) framework for 110 Call Center operators at the Bogor Police Resort (Polres). A qualitative methode with a case study design was employed. Data were collected through in-depth interviews, non-participant observation, and documentation studies, which were then analyzed using the interactive model by Miles, Huberman, and Saldaña. The results indicate that the heterogeneity of reports requires operators to utilize agile thinking, while exposure to secondary trauma triggers emotional exhaustion. Therefore, there is an urgent need to escalate technical capacities (digital application literacy) and strengthen Psychological Capital. This study recommends an evolution of training towards a Learning Organization via experiential learning (crisis simulation), peer-mentoring, and the integration of Psychological First Aid (PFA). The comprehensive implementation of L&D strategies is believed to accelerate the police's digital transformation, enhance public trust, and realize the paradigm of public service excellence.